Sex Differences in Biopsy-Confirmed Diabetic Kidney Disease - Wang, Yiting; Zhang, Jue; Zhang, Junlin; Wu, Yucheng; Zhang, Rui; Ren, Honghong; Cooper, Mark E.; Liu, Fang (Frontiers in Endocrinology, 2021)
Background: To investigate the association between sex differences and end-stage kidney disease (ESKD) in patients with biopsy-confirmed diabetic kidney disease (DKD). Method: We performed a retrospective cohort study. A total of 336 patients with biopsy-confirmed DKD who were followed up for at least 12 months were enrolled. Baseline clinical and pathological data at the time of biopsy were collected. ESKD was defined by an estimated glomerular filtration rate of <15 mL/min/1.73m2 or initiation of renal replacement therapy. The association between sex differences and ESKD was assessed using the log-rank test and Cox regression. Result: There were 239 (71%) male and 97 (29%) female patients in our cohort. Female patients had higher systolic blood pressure, total cholesterol and low-density lipoprotein cholesterol levels compared with male. There was a lower proportion of female patients in the very high risk grade according to the chronic kidney disease categories (37% of female vs. 44% of male). During a median follow-up time of 20 months, 101 (57.7%) male and 43 (44.3%) female entered into ESKD, with no significant difference by the log-rank test (P>0.05). Univariate [male: hazard ratio (HR) (95% confidence interval (CI)), 1.005, (0.702-1.439) ] and multivariable ([male: HR (95%CI), 1.164, (0.675-2.007) ] Cox regression further showed that sex difference was not significantly associated with ESKD. Conclusion: Female patients had the higher systolic blood pressure, total cholesterol, LDL-C, compared with male patients. However, there was no significant association was observed between sex difference and ESKD in our study.